Comparative Study on Tax Collection and Tax Administration System of Indonesia and Malaysia - Stephania Stephania; Yenni Martok (Journal of Accounting and Management Innovation, 2022)
This study aims to identify and analyze the application of tax collection and taxation systems in Indonesia and Malaysia, to find out and analyze the comparison of tax collection and taxation systems used in Indonesia and Malaysia and to identify and analyze the efforts made by Indonesia and Malaysia in improving compliance. taxes in that country.The research method used is qualitative research, which is used to examine the condition of natural objects, where the researcher is the key instrument, in the form of: documentation data on tax management systems, tax collection, implementation of tax results in two countries, namely Indonesia and Malaysia. Data collection is done by triangulation (combined), data analysis is inductive, and the results of qualitative research emphasize meaning rather than generalization.Aftter the discussion, thre are 3 systems in the application of tax collection and taxation systems in Indonesia with a tax collection system , those are self-assessment system, official assessment system and withholding assessment system. The  tax system in Malaysia is based on income tax in general, which is imposed on a territorial basis and the only income originating from Malaysia which is subject to tax. There are also comparison of tax collection and the taxation system used in Indonesia and Malaysia which shows a striking difference, the first in the use of the tax system. Indonesia adheres to the self-assessment system while Malaysia adheres to the Preceding Year Base of Assessment with the Current Base  of Assessment.Keyword: Tax Collection, Tax Administration System